2021
DOI: 10.1093/jxb/erab543
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions in fatty acid elongase complexes are important for very-long-chain fatty acid synthesis

Abstract: Fatty acid elongase (FAE), which catalyzes the synthesis of very-long-chain fatty acids (VLCFAs), is a multiprotein complex; however, little is known about its quaternary structure. In this study, BiFC and/or yeast two hybrid (Y2H) assays showed that 1) homo-interactions were observed in β-ketoacyl-CoA synthases (KCS2, KCS9, and KCS6), Eceriferum2-like proteins [CER2 and CER2-Like2 (C2L2)], and FAE complex proteins (KCR1, PAS2, ECR, and PAS1), except for CER2-Like1 (C2L1). 2) Hetero-interactions were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…An additional family of the AtCER2-like proteins (including AtCER2, AtCER2-like1/CER26, and AtCER2-like2/CER26-like) belong to the BAHD acyltransferase family (named for the first four enzymes described in this clade: benzylalcohol O -acetyltransferase, anthocyanin O -hydroxycinnamoyltransferase, N -hydroxycinnamoyl/benzoyltransferase, and deacetylvindoline 4- O -acetyltransferase) and are considered to be involved in the synthesis of VLCFAs longer than C28 as they interact specifically with AtKCS6/CER6 or AtKCS5/CER60. , Recently, bimolecular fluorescence complementation analysis has shown that AtCER2-like proteins directly interact with AtKCS6/CER6 . In addition to Arabidopsis, OsCER2-like/CER26 and OsKCS6/CER6 genes from rice have been identified and characterized.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…An additional family of the AtCER2-like proteins (including AtCER2, AtCER2-like1/CER26, and AtCER2-like2/CER26-like) belong to the BAHD acyltransferase family (named for the first four enzymes described in this clade: benzylalcohol O -acetyltransferase, anthocyanin O -hydroxycinnamoyltransferase, N -hydroxycinnamoyl/benzoyltransferase, and deacetylvindoline 4- O -acetyltransferase) and are considered to be involved in the synthesis of VLCFAs longer than C28 as they interact specifically with AtKCS6/CER6 or AtKCS5/CER60. , Recently, bimolecular fluorescence complementation analysis has shown that AtCER2-like proteins directly interact with AtKCS6/CER6 . In addition to Arabidopsis, OsCER2-like/CER26 and OsKCS6/CER6 genes from rice have been identified and characterized.…”
Section: Introductionmentioning
confidence: 80%
“…Previous research has revealed that they are all localized to the ER and catalyze the biosynthesis of VLCFAs beyond C26 by interacting with KCS6. However, they exhibit different organ expression specificity and substrate specificity. ,,, AtCER2 is expressed in almost all aerial organs, and its mutation causes a significant reduction of multiple C29 wax monomers on Arabidopsis stems, including the C29 alkane, C29 ketone, and the C29 secondary alcohol , Since AtCER26L is mainly expressed in anthers, its mutation does not cause changes in the wax composition on the Arabidopsis rosette leaves.…”
Section: Discussionmentioning
confidence: 99%
“…For the cuticular wax biosynthesis, plastid-derived C16 and C18 acyl-CoAs were first elongated to VLC (up to C34) acyl-CoAs by the FAE complex and the ECERIFERUM2 (CER2) protein ( Haslam et al, 2015 ). It was recently demonstrated that protein-protein interactions in the FAE complex, including extensive protein–protein interactions among Arabidopsis FAE complex proteins KCR1, PASTICCINO2 (PAS2), ECR, and PAS1, as well as specific interactions between KCS9 and PAS2 or ECR, are essential to the VLC acyl-CoAs elongation ( Kim et al, 2021 ). These elongated VLC acyl-CoAs were then either converted into n -alkanes, n -aldehydes, secondary alcohols, and ketones via the alkane-forming pathway or modified into primary n -alcohols and esters through the alcohol-forming pathway.…”
Section: Cuticle Biosynthesis In Model and Crop Plantsmentioning
confidence: 99%
“…VLCFAs, as hydrocarbon chains containing more than 20 carbon atoms, are the precursors of different kinds of lipids such as phospholipids and sphingolipids, and function in various physiological processes (Bach et al, 2011 ; Wang et al, 2018 ; Zhukov, 2018 ; Kim et al, 2021 ). Elo1, Elo2, and Elo3 are three fatty acid elongases in yeast.…”
Section: Introductionmentioning
confidence: 99%